Aplikasi Keamanan Pintu Berbasis Arduino Uno R3 Atmega 328p Menggunakan Fingerprint Dan Ultrasonik - Hendi Setiawan; Darmawan Mega Permana; Agus Fitro Handoko (Jurnal Bangkit Indonesia, 2019)
In door security systems, many have used, even more sophisticated, but with sophistication or a better security system but there are also drawbacks, namely the cost to implement it is very expensive. Therefore we need a door security system which is cheaper and more affordable in its implementation. In this research, the writer raises a case that is making a door security system that can be applied and affordable in operational costs. This door security system uses the Arduino application as an uploader, then a fingerprint sensor and an ultrasonic sensor as the tools used. This door security system can only be implemented if this system is supplied with electricity and can only be accessed against registered fingerprints